Heterogeneous agent-enabled decision system for evaluating Green IT performance in industrial environments - Bokolo, Anthony Jnr; Mazlina, Abdul Majid; Awanis, Romli (Taylor & Francis, 2018)
This article implements heterogeneous agent-enabled decision systems that provide a Green IT nomenclature to be implemented by IT practitioners in an industrial environment. Moreover, the system evaluates and ranks the current Green IT performance in an industrial environment. Data was collected using questionnaire from selected industries in Malaysia and analyzed using Statistical Package for Social Science (SPSS) by applying descriptive and factor analysis to test the usability of the agentbased evaluating system. Respectively, ﬁndings from this study indicate that the heterogeneous agents facilitate decision-making of IT practitioners by providing information on how they improve their current Green IT practice towards addressing environmental issues. Besides, the system reduces the time and cost of Green IT practice implementation by capturing, retaining and reusing past knowledge for improved decisionmaking. Practically, the system provides decision support by providing best-practice recommendations to IT practitioners on Green IT nomenclature to be implemented in their industrial operations.